Efficiency, Performance, and Potential Improvement of Indonesian Rural Banks During Covid-19 Pandemic - Rusydiana, Aam Slamet; Uula, Mimma Maripatul; Maulida, Syahdatul; Aufa, Aufa; Kanz, Raihan Agra Dharana (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2023)
The objective of this study is to examine the efficiency, performance, and scope for enhancement of Rural Banks (BPRs) and Sharia Rural Banks (BPRSs) in Indonesia, particularly in the context of the Covid-19 pandemic, in order to support national economic recovery. The research sample consisted of 77 BPRs and 52 BPRSs in Indonesia over the period of 2016-2020. The analytical approach employed was a non-parametric method called Data Envelopment Analysis (DEA), utilizing secondary data obtained from financial bank statements. The input variables encompassed fixed assets, operational costs, and third-party funds, while the output variables included the amount of financing provided and operating income. The findings of the study reveal a fluctuating trend in the performance of BPRs and BPRSs in Indonesia from year to year. According to the CRS and VRS scores, the efficiency level of BPRs remained stable during the Covid-19 pandemic, whereas BPRSs experienced a decline in efficiency. Consequently, this study concludes that BPRs exhibit superior efficiency compared to BPRSs in Indonesia. Moreover, the analysis of potential improvements indicates that the most significant source of inefficiency lies within the output variables: financing and operating income. Furthermore, benchmarking analysis reveals that the efficiency of both BPRs and BPRSs was higher during the periodof 2016–2019 compared to 2020.